Solving optimal reactive power problem by hurricane search optimization algorithm - Kanagasabai Lenin (Institute of Advanced Engineering and Science, 2021)
In this paper proposed hurricane search optimization (HSO) algorithm is proposed to solve optimal reactive power problem. An upward motion of air is caused due to release of heat which creates a low-pressure zone and by the rotation of the earth that is set into spin. In this spiraling airflow when energy is high then hurricane is created. Projected HSO algorithm design is based on the examination of the horizontal wind structure in a hurricane and how the wind parcels the progression in the neighboring atmosphere. A mixture of wind models has been developed for past few years to Backtesting and to compute hurricane exterior wind fields. Proposed HSO algorithm has been tested in standard IEEE 30, 57bus test systems and simulation results show the projected algorithm reduced the real power loss considerably.